Utilization of Learning Videos Based on Japanese Occupation Materials in Indonesia as Digital History Learning Objects - Muhammad Dwi Kurniadi; Rizki Ananda Hsb; Zulkarnain Zulkarnain (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research aims to analyze the benefits of Japanese Occupation Material-based Learning Video in Indonesia as a Digital History Learning Object whose problem formulations include :(1) How can Japanese Occupation Materials in Indonesia become objects of historical learning? (2) How can the use of material-based historical learning videos in Indonesia become objects of digital history learning? To answer both problems, the authors used a qualitative approach with a literary study method that collected several articles from previous research results as well as related to research themes. From the results of the research obtained that japanese occupation materials in Indonesia can be used as objects of historical learning because it corresponds to the needs of core competencies and basic competencies of history learning in high school, as well as to improve the nationalist attitude of students, by herding students to imagine the material of occupation in Indonesia through learning videos so that students can see the events of japanese occupation in Indonesia directly. Then based on previous research also explained that the results of the study using video learning based on japanese occupation materials in Indonesia is in effective value to be used as a medium of historical learning.